التأمين الاجتماعي للمرض في التشريع الجزائري - مقداد بلعيد; محمد نصر الدين خياري (My University, 2018)
Summary: This research aims to study the social insurance of the disease in Algerian legislation Law No. 11/83 of 21 Ramadan, 1403 A.H., corresponding to July 02, 1983, on modified and complete social insurance. This is in accordance with article 2 of the Law on Social Security, which provides for the reconciliation of Algerian legislation in the provision of adequate insurance coverage for the insured, and the Law No. 83/08 of July 1993 on the settlement of the Medical Social Security Dispute of 08. On social security disputes where social insurance aims at the risk of illness is aimed at diversifying the performance to the socially insured in kind and in cash, where in-kind performance includes all treatment services medical, hospital and preventive performance. This is exemplified by compensation for wages lost due to illness. However, the scope of access to such performance is limited by the obligations, conditions and procedures of such diversification in the submission of the performance. This includes not only the social insured in particular but also those with the rights of the social insured. s rights ", which reflects the reality of the strategic dimension aimed at providing the greatest social protection by the Algerian legislature both to the believer and to the holder of his rights, This provision is reflected in the legal arsenal established by Algerian legislation, laws, executive decrees, ministerial decisions and leaflets (...). Also through medical coverage, however, as we have also concluded, despite benefiting from these privileges provided by the legislator to the socially insured person in this area, the latter may challenge the decisions of the Social Security Authority of its Medical Adviser concerning his state of health, As a consequence of a medical dispute between him and the interests of the Social Security Authority, this dispute may rise to a medical dispute and to settle this dispute between the parties. The legislator has set up two roads through internal settlement by means of medical expertise and the qualified state disability commission, which is the origin and judicial settlement. ....................... ملخص : يهدف هذا البحث الى دراسة التأمين الاجتماعي للمرض في التشريع الجزائري ، حيث يعتبر التأمين عن هذا الخطر مشمول التغطية ضمن المخاطر الأربعة المدرجة في قانون رقم 11/83 المؤرخ في 21 رمضان عام 1403هـ الموافق 02 يوليو 1983 المتعلق بتأمينات الاجتماعية المعدل والمتمم وهذا وفقا لما ورد في نص المادة الثانية منه وهذا بغرض الوصول الى توفيق المشرع الجزائري في توفير التغطية الكافية بالنسبة للمؤمن له أم لا وكذا الى الطرق التي انتهجها المشرع في سبيل تسوية المنازعة الطبية في مجال الضمان الاجتماعي والذي كفل مسألة تنظيمها وتسويتها بموجب قانون 15/83 المؤرخ في 02 يوليو 1983 المتعلق بمنازعات في مجال الضمان الاجتماعي المعدل والمتمم وقانون 08/08 المؤرخ في 2008/2/23 ، المتعلق بمنازعات في مجال الضمان الاجتماعي حيث يهدف التأمين الاجتماعي للخطر المرض الى التنويع في تقديم الأداءات الى المؤمن له اجتماعيا العينية منها والنقدية حيث تتضمن الأداءات العينية في مضمونها كافة الخدمات العلاجية ، والطبية ، والاستشفائية ، والوقائية، أما الأداءات النقدية فيتجسد ذلك من خلال التعويض عن الأجر المفقود بسبب المرض غير أن مجال الاستفادة من هذه الأداءات مقيدة بالالتزامات وشروط واجراءات هذا التنويع في تقديم الأداءات لم يشمل فقط المؤمن له اجتماعيا على وجه الخصوص بل تعدى هذا الأمر الى ذوي حقوق المؤمن له اجتماعيا، وهو ما يعكس حقيقة البعد الاستراتيجي الهادف الى توفير أكبر قدر من الحماية الاجتماعية من قبل المشرع الجزائري سواء للمؤمن له أو ذو حقوقه ، هذا التكفل يترجم مدلوله في هذا المجال من خلال الترسانة القانونية التي وضعها المشرع الجزائري قوانين ، مراسيم تنفيذية، قرارات وزارية، مناشير (...) وكذلك من خلال التغطية الطبية ، الا أنه وكما خلصنا أيضا بالرغم من الاستفادة من هاته الامتيازات التي وفرها المشرع الى المؤمن له اجتماعيا في هذا المجال قد يعترض هذا الأخير ضد قرارات هيئة الضمان الاجتماعي الصادرة عن مستشارها الطبي التابع لها في يخص حالته الصحية، مما يترتب خلاف طبي بينه وبين مصالح هيئة الضمان الاجتماعي هذا الخلاف قد يرتقي الى نزاع طبي و لتسوية هذا النزاع المثار بين الطرفين عمد المشرع الى وضع طريقين وذلك عن طريق التسوية الداخلية بأليتيها الخبرة الطبية ولجنة العجز الولائية المؤهلة التي تعتبر هي الأصل والتسوية القضائية التي تعتبر الاستثناء. ولقد اعتمدنا في دراستنا على المنهج الوصفي و آلية التحليل، أما فيما يخص تقسيم البحث محل الدراسة فلقد قسم الى فصلين الفصل عالجنا فيه ماهية التأمين عن المرض وكيفية تعويضه أما الفصل الثاني فلقد تطرقنا إلى تسوية المنازعة الطبية في مجال الضمان الاجتماعي في الجزائر. .......................... Résumé : Cette recherche vise à étudier l’assurance sociale de la maladie dans la législation algérienne Loi n. 11/83 du 21 Ramadan, 1403 A.H., correspondant au 2 juillet 1983, sur l’assurance sociale modifiée et complète. Ceci est conforme à l’article 2 de la loi sur la sécurité sociale, qui prévoit le rapprochement de la législation algérienne dans la fourniture d’une couverture d’assurance adéquate pour l’assuré, et la loi n° 83/08 de juillet 1993 relative au règlement du litige médico-social du 08. En ce qui concerne les litiges de sécurité sociale où l’assurance sociale vise le risque de maladie, l’objectif est de diversifier la prestation aux assurés sociaux en nature et en espèces, où la prestation en nature comprend tous les services de traitement, médicaux, hospitaliers et préventifs. Cela est illustré par l’indemnisation des salaires perdus en raison de la maladie. Toutefois, la portée de l’accès à cette exécution est limitée par les obligations, les conditions et les procédures de cette diversification dans la soumission de l’exécution. Cela inclut non seulement les assurés sociaux en particulier, mais aussi ceux qui ont les droits de l’assuré social. s droits ", qui reflète la réalité de la dimension stratégique visant à fournir la plus grande protection sociale par le législateur algérien à la fois au croyant et au titulaire de ses droits, Cette disposition se reflète dans l’arsenal juridique établi par la législation algérienne, décrets exécutifs, décisions ministérielles et dépliants (...). Mais aussi par le biais de la couverture médicale, comme nous l’avons également conclu, bien que bénéficiant de ces privilèges accordés par le législateur à l’assuré social dans ce domaine, celui-ci peut contester les décisions de l’autorité de sécurité sociale de son conseiller médical concernant son état de santé, à la suite d’un différend médical entre lui et les intérêts de l’autorité de sécurité sociale, ce litige peut donner lieu à un litige médical et régler ce litige entre les parties. Le législateur a mis en place deux routes à travers le règlement interne par le biais de l’expertise médicale et la commission d’invalidité de l’État qualifié, qui est l’origine et le règlement judiciaire.